An approach to product assortment planning using aggregate data - Wyson, James (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Product assortment is one of the basic decisions retailers make but due to its complexity, no dominant solution has been adopted. Current research on the topic is divided among two fields with different concentrations; marketing focused on the consumers and operations research on the retailer. To create profitable assortments which match consumer preferences, this thesis describes a three-step decision support system for product assortment planning which combines techniques from both marketing and operations research. Using demand estimates from a marketing model as inputs to a genetic algorithm with a news-vendor objective function, it determines which product assortments a retailer should offer to maximize profits. The proposed system generates assortments either comparable to or better than those generated by two existing heuristics in both the simulated and industry data sets used.
Thesis (M.S. Industrial Engineering Major in Operations Research)--University of the Philippines, Diliman
Keywords: Bundling (Marketing); Consumer's preferences